Peran Dinas Perikanan Dalam Meningkatkan Pendapatan Masyarakat Nelayan - Nur Jalal; Syahruddin Syahruddin; Erwin Nugraha Purnama (Universitas Musamus, Merauke, Papua, 2022)
The purpose of the study was to describe the role of the Fisheries Service of Merauke Regency in Increasing the Income of Fishermen, Samkai Village, Merauke Regency. This study uses a qualitative method with a descriptive approach, while the data analysis technique uses three stages: data reduction, data presentation, and efforts to draw conclusions or verification. The results of this study indicate that the role of the Merauke District Fisheries Service in increasing the income of the fishing community in Lampu one, Samkai sub-district, has not been implemented properly. This has an impact on the empowerment of fishing communities in order to increase their income. From several research indicators used, in terms of labor resources, there is still a lack of knowledge and skills in the use and repair of fishing gear, due to the lack of maximum guidance from the service and the lack of responsiveness of the fishing community. The lack of capital for the fishing communities, as well as limited business capital assistance from the agency, have not been able to increase significantly. Fish catching facilities and techniques are still simple, many use tools or traditional boats to catch fish, also equipment assistance from the service has not been able to fully provide assistance to fishing communities due to the limited government budget. The marketing and financial management and management techniques owned by fishing communities in order to increase their income are still lacking, also in terms of increasing skills from the service, it is not intensive and unsustainable.